Komparasi Media Aplikasi Spacedesk dengan Media LCD dalam Meningkatkan Minat Belajar Siswa SMAN 2 Palopo - Rahman, Abdul; Rahmah, Nur; Lestari, Alia (Circle: Jurnal Pendidikan Matematika, 2025)
This study aims to compare the use of spacedesk application media and LCD media in increasing students' interest in learning at SMAN 2 Palopo. This type of research is a comparative experiment focusing on the comparison of two different samples. The sampling was conducted using a cluster random sampling technique, with the sample including class XII IPA 1 with 33 students and class XII IPA 2 with 26 students. Data were collected through questionnaires and documentation. The data were then analyzed using an independent sample T-test. The results of this study indicate that the learning interest of students in class XII IPA 1 using the Spacedesk application media successfully enhanced students' attention, although not significantly. However, it did not succeed in improving students' enjoyment, engagement, or interest. In contrast, the learning interest of students in class XII IPA 2 using LCD media successfully enhanced students' enjoyment, interest, and attention. Additionally, it improved student engagement, though not significantly. The independent sample T-test showed a significance value of  sig.=0,000 <  5%, indicating a difference in the effectiveness of the Spacedesk application media versus LCD media in enhancing students' learning interest. The practical implication of this research is that schools and teachers can implement LCD-based learning methods to enhance students' interest in learning, as schools have adequate electrical installations, classrooms, and LCD media.